Genetic Databases and their Potential in Pharmacogenomics - Lagoumintzis, George; Poulas, Konstantinos; P. Patrinos, George (Current Pharmaceutical Design, 2010)
The completion of the human genome sequencing project and the establishment of new methods for the detection of point mutations have lead to a remarkable increase of sequence variants identification in a growing number of genes. As a result of this, a new field of research has emerged, pharmacogenomics, which deals with the influence of genetic variation on drug response by correlating gene expression or single-nucleotide polymorphisms with a drug's efficacy or toxicity. Genetic databases are continuously updated online repositories of mutation data, described for a single or more genes or specifically for a population or ethnic group. Genetic databases can also fulfil the mission of pharmacogenomics by helping elucidate gene function, estimate the prevalence of genes in populations, differentiate among subtypes of diseases, trace how genes may predispose to or protect against illnesses, and improve medical intervention. Therefore, it is expected that genetic databases will gradually assume an increasing importance in all aspects of genome medicine. This article aims to provide an update of the current and emerging types of genetic databases relevant to the field of pharmacogenomics. Moreover, the key elements that are holding back the field as well as the challenges that should be addressed in the near future are also commented.
Keywords: Databases